2000
DOI: 10.1046/j.1537-2995.2000.40101228.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of the need for allogeneic blood transfusion in lung cancer surgery

Abstract: A predictive model can preoperatively identify patients at risk for needing ABT in lung cancer surgery. The model could be utilized to tailor blood-sparing intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(61 reference statements)
0
9
0
1
Order By: Relevance
“…The need for blood transfusion within 30 days following surgery has been reported as ranging from 16-25% of all patients receiving lung cancer resection [1][2][3][4] and exceeded 40% in the present study, which focused on pneumonectomy, although a rather restrictive and homogeneous transfusion strategy was used over the study period. The transfused patients of the present study required large amounts of blood products, suggesting that they would not have been able to avoid such a treatment.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The need for blood transfusion within 30 days following surgery has been reported as ranging from 16-25% of all patients receiving lung cancer resection [1][2][3][4] and exceeded 40% in the present study, which focused on pneumonectomy, although a rather restrictive and homogeneous transfusion strategy was used over the study period. The transfused patients of the present study required large amounts of blood products, suggesting that they would not have been able to avoid such a treatment.…”
Section: Discussionmentioning
confidence: 58%
“…here have been very few clinical trials evaluating the blood-product needs in patients subjected to major thoracic oncological surgical procedures [1][2][3][4]. The issue is of clinical relevance since outcome data on transfusion therapy have not always been favourable, particularly in the areas of post-operative infection, systemic inflammatory response syndrome, multiple organ failure and finally mortality.…”
mentioning
confidence: 99%
“…In this study, we identified that advanced age, female sex, diabetes with chronic complications, and metastatic tumor were consistently predictive of transfusion during spinal surgery, including any allogeneic transfusion and RBC transfusion. Previous data regarding associations between patient characteristics and outcomes in high‐risk surgical patients have been derived primarily from clinical trials, chart review, or administrative databases from a single institution 7‐14 . In such studies of patients undergoing orthopedic surgery, patient factors that have been identified to be associated with increased blood transfusion include baseline Hb, 7,8,11,13 autologous donation status, 8,13 patient weight, 8 patient blood volume, 11 presence of tumor, 13 pulmonary disease, 13 type of surgery, 8,13 and primary versus revision surgery 8 …”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Previous data regarding associations between patient characteristics and outcomes in high-risk surgical patients have been derived primarily from clinical trials 7 and may not reflect patient risk characteristics in the general population. Other studies have used administrative databases or chart review [8][9][10][11][12][13][14] to evaluate the association between patient characteristics and transfusion at a single institution. By using a statewide administrative database, we conducted a population-based study to evaluate the factors that predict transfusion for a large number of patients undergoing spinal surgery at multiple hospitals.…”
mentioning
confidence: 99%
“…Patient factors drive the decision for some RBC transfusions [14][15][16][17][18][19]; however, non-patient level factors may also be important. Specifically, studies suggest that surgeon casevolume is associated with incidence of transfusion among patients undergoing spine [20], colorectal [21], and cardiac surgery [22].…”
Section: Introductionmentioning
confidence: 99%